Preparation And Properties Of Sepiolite-Filled Ethylene Propylene Diene Terpolymer Composites - Mohd Zaini, Nurul Aizan (2020)
The role of clays as fillers in rubber composites is unquestionably important due to their abundance, low cost, light colour, and ability to enhance the strength and stiffness of rubber. However, differences between the compatibility of the hydrophilic clay and the hydrophobic rubber, which would result in a poor dispersion, remains as a challenging problem in industrial applications. This study was conducted to determine the potential of incorporating sepiolite (Sep) as a filler in ethylene propylene diene terpolymer (EPDM). EPDM/Sep composites were prepared with Sep loadings of 0–70 parts per hundred of rubber (phr) using a two-roll mill. The results indicated improvements in the tensile and dynamic mechanical properties, swelling resistance and crosslink density, thermal stability, and flammability resistance of the sepiolite-filled composite compared with the unfilled composite. The homogenous dispersion of sepiolite particles in the EPDM matrix and the formation of zigzag structures, especially at 60 phr, were the main reasons for the improved mechanical properties of the composite, which were confirmed by the morphological studies. The formation of a protective layer, which acted as a barrier against heat transfer into the deeper layers, had enhanced the flammability resistance of the composites. In the study of sepiolite hybridised with carbon black (CB), silica, or calcium carbonate (CaCO3), five different compositions were prepared, with EPDM/Sep at 30 phr as a control composite. EPDM/Sep/CB displayed the highest tensile strength, thermal stability, and improved flammability resistance. These results were influenced by the ability of CB to disperse well and form protective layers that could act as a mass transport barrier in the matrix. Significant findings in this work indicated that silica and CB were able to be hybridised with sepiolite, while sepiolite could be a potential substitute for CaCO3 in the EPDM composites. Meanwhile, the utilisation of glut palmitate (GP) salt and (3-aminopropyl) trimethoxysilane (APTMS) as coupling agents in the EPDM/Sep composites have successfully enhanced the tensile strength and elongation at break, the rubber-filler interaction, and dynamic mechanical properties. The enhanced rubber-filler interaction indicated that the presence of GP and APTMS have improved the compatibility and interaction between Sep and EPDM matrix, as supported by the FTIR results. Studies on different vulcanisation systems revealed that the highest tensile and dynamic mechanical properties were exhibited by the sulphur system, followed by the mixed curative and peroxide system, whereas the highest thermal stability and flammability resistance were demonstrated by the peroxide system.